Timing Differences in Eye-Hand Coordination Between Experienced and Inexperienced Tennis Players. - Mahadas, Kausalendra; Mohammand, Faisal; Samim, Haris; Jannapureddy, Shruthi; Hung, George K.; Ciuffreda, Kenneth J. (Optometry & Visual Performance, 2015)
Background: Tennis is one of the most popular sports in the U.S. However, there is relatively little objective investigation of the underlying body and racquet dynamics. In the present study, timing differences in eye, head, and racquet motions during the tennis stroke were investigated. Methods: Two experienced and two inexperienced young-adult tennis players participated in this pilot study. The task was to hit the center of a multi-ring bull's-eye target located 3 meters away at a height of 1.37 m. Each subject performed 40 forehand and 40 backhand trials. The eye, head, and racquet motions were recorded via wireless sensors. In addition, a digital video recorder was used to record the trials for offline detailed analysis. Results: In all subjects, head movement initiation occurred prior to both eye motion and racquet impact for both the forehand and backhand strokes. In addition, eye movement initiation occurred before racquet impact in experienced players, but after racquet impact in the inexperienced players. Conclusions: Head rotation may be an important component in the neuro-motor sequence of movements for generating body torque to provide power in the groundstroke. Also, the experienced player may use a more optimal, pre-programmed strategy for attaining and maintaining both consistency and accuracy. These new findings provide insight into how training of eye-hand coordination is revealed in the timing differences during the racquetimpact phase of the groundstroke.